Facile and scalable synthesis of baphicacanthin A by a two-pot procedure. Issue 9 (3rd May 2023) - Cuan, Yalong; Li, Wenhao; Dou, Yingchao; Yang, Guanyu
Abstract: Facile two-pot total synthesis of baphicacanthin A, a natural phenoxazinone alkaloid isolated from the roots of Baphicacanthus cusia which has been utilized as a traditional chinese medicine to effectively treat disease caused by coronavirus, has been developed from simple and commercially available starting materials. Catalytic aerobic oxidative cross-cyclocondensation of equimolar 2-aminophenol and 3-methoxy-2-hydroxylphenol in water was used to construct the key molecular skeleton 2-hydroxy-3 H -phenoxazin-3-one. Gram scale synthesis was realized in 80% overall yield with practical convenience. Graphical Abstract: UF0001